Checklist of Omophoita Chevrolat, 1836 (Coleoptera: Chrysomelidae: Galerucinae: Alticini) and diagnoses for some species from southern Brazil: notes on the taxonomic history, redescriptions and new records - Begha, Bruno Piotrovski; Anjos, Camila Alves Dos; Santos, Mateus Henrique; Prado, Laura Rocha (Zootaxa, 2023)
Morphological descriptions, taxonomic history and distribution data of Omophoita species recorded for southern Brazil (states of Paraná, Santa Catarina and Rio Grande do Sul) are presented. Through the analysis of the existing literature, databases, loaned material, and specimen collecting, we studied seven species of Omophoita recorded for southern Brazil: O. communis (Bechyné 1959), O. equestris (Fabricius 1787), O. magniguttis (Bechyné 1955), O. octoguttata (Fabricius 1775), O. personata (Illiger 1807), O. sesquilunata (Klug 1829), and O. sexnotata (Harold 1876). We report O. sesquilunata for this region for the first time. Updated morphological descriptions, including novel information for male and female genitalia are presented for those taxa with dissected specimens.